Leadership and Management of the Multicultural Education Curriculum at Senior High School - Suncaka, Eko (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to reveal several things, namely: First, how is the practice of multicultural leadership at SMAN 1 Gadingrejo Pringsewu Lampung; Second, how is the management of multicultural curriculum planning; Third, how is the teaching and learning process based on multiculturalism? His type of research is qualitative. The research approach uses phenomenology. The research subjects are the principal, the teacher council, and Santri's parents. Methods of data collection using in-depth interviews, observation, and documentation The data analysis technique uses triangulation. The results of the study show that: first, aspects of the principal's leadership are appropriate and work in an educative manner, and with managerial models, administrators, supervisors, leaders, innovators, and motivators who are disciplined and prioritize students' diverse backgrounds; Second, the planning aspect of the principal at SMAN 1 Gadingrejo has characteristics: there are goals to be achieved, current circumstances, alternative choices, priorities, and strategies used to achieve goals; Third, aspects of the actualization of multicultural education management at SMAN 1 Gadingrejo are detailed through good management of educational staff, relevant learning curricula, good school financial management, facilities and infrastructure that suit student needs, well-established relations with the community, and values of tolerance like nobleness, honesty, and the spirit of achievement; Fourth, the evaluation aspect at SMAN 1 Gadingrejo has characteristics: there are quality norms and target assessment, it is directly driven by what is important in the view of all teachers and staff, the chairperson only gives the title, the assessment is planned methodically, the assessment is open, and there is an exchange of sentiments from members.